miR-212 Promotes Cardiomyocyte Hypertrophy through Regulating Transcription Factor 7 Like 2 - Jinxia Yuan; Guoliang Yuan (Mediators of Inflammation, 2022)
To explore the role and possible mechanism of miRNA-212 in heart failure (HF). The rat model of abdominal aortic constriction was constructed, the changes of myocardial morphology were observed by hematoxylin-eosin (HE) staining, and the hypertrophy-related marker molecules were detected by quantitative real-time polymerase chain reaction (qRT-PCR). At the cellular level, phenylephrine and angiotensin II were added to induce cardiomyocyte hypertrophy. The overexpression of miR-212 adenovirus was constructed, and the expression of miR-212 was overexpressed, and its effect on cardiac hypertrophy (CH) was detected by immunofluorescence and qRT-PCR. Then, the mechanism of miR-212 regulating CH was verified by website prediction, luciferase reporter gene assay, qRT-PCR, and western blotting assay. In the successfully constructed rat model of abdominal aortic constriction and cardiomyocyte hypertrophy, ANP and myh7 were dramatically increased, myh6 expression was decreased, and miRNA-212 expression was increased. Overexpression of miRNA-212 in cardiomyocytes can promote cardiomyocyte hypertrophy, while knocking down miR-212 in cardiomyocytes can partially reverse cell hypertrophy. In addition, miR-212 targets TCF7L2 and inhibits the expression of this gene. miRNA-212 targets TCF7L2 and inhibits the expression of this gene, possibly through this pathway to promote cardiomyocyte hypertrophy.